Les flux technologiques interindustriels : une analyse exploratoire du potentiel canadien - Dulude, Louise (L'Actualité économique, 1982)
AbstractIn this paper, an analysis of patents issued in Canada is made. The results of this analysis induce the author to question a hypothesis that was implicit in previous studies. According to this hypothesis, inventions used by a given industry origin in the same industry and only the technological effort of an industry can lead to inventions useful to that industry. The results suggest that a large number of industries profit from technology developed by a small number of industries.